ANALISIS FAKTOR YANG MEMPENGARUHI KINERJA OPERASIONAL PERUSAHAAN FREIGHT FORWARDING DALAM MENUNJANG KEGIATAN EKSPOR - Kholid Mawardi (Jurnal Ekonomi, Bisnis dan Manajemen, 2022)
This study aims to analyse the significance factors of Sea Export Process, Forwarding Responsibility, and Warehouse Handling Process towards the operational performance of Raja abadi branch Company in Semarang. This study is performed to the company's staff members as the population of 70 respondents. The data collection involves observations, literary reviews, interviews, documentations, and questionaires. Furthermore, the analysis technique used in this study is based on the result of research and multiple analysis using SPSS v.23 program. Based on the results of the research, the following equations are generated : Y = 2,752 + 0,268X1 + 0,342X2 + 0,184X3 + µ Based on the multiple linear regression equation, the study found out that the most dominant variable in the operational performance of the company is the Forwarding Responsibility variable with the regression coeficiency of 0,342. Furthermore, the determinated coeficiency (adjusted R square) showed a result of 0,707 or 70,7%. This means the operational performance of the company is governed by the variables of Sea Export Process, Forwarding Responsibility, and Warehouse Handling Process by 70,7% as well as other factors by 29,3%. Therefore, it is found that Air Export Process, Forwarding Responsibility, and Warehouse Handling Process played a positive and significance role for the operational of the Raja abadi branch Company in Semarang.